Pemikiran Filsafat Carl Gustav - Setiawan, Romi (Tasamuh: Jurnal Studi Islam, 2016)
Jung’s theory of the complex which is about a set of psychic “psycho-emotional” (feeling toned) that is pressed is the first experimental investigation results in collaboration with Franz Rikin and other scientists in 1904, with the title “Diagnostische Assoziationsstudien”. This work is popular and as a bridge a meeting with Sigmund Freud in 1907 in his writings about dream interpretation, Jung got endorsement on his investigation, Even Freud eventually realized that Jung is the “crown prince” of psychoanalysis and the heir to his throne. Their relationship is not limited to the more intimate friendship, more than it is psychologist’s community. In October 2006 Freud sent his work recently completed entitled Short papers on the theory the neurosis. With Jung reply letter, correspondence conducted in earnest, a very friendly exchange and intimate of the two thinker’s personal as well as scientific reflections for almost more than seven years. But Jung did not fully set and adhered to the theory of Freud. Their relationship was strained in 1909, when both of them went to America. In a meeting, both salty mulls over their dreams, and Freud began to refute the analysis in a way, according to Jung is not elegant. Finally he gave up and suggested that they be stopped debate, if she does not want her authority destroyed. Jung was very disappointed with this incident. The longer Jung increasingly is keen to explore the mythological symbols and religious symbols. This article elaborates Jung’s philosophy of human relations and religion.